FACTORS THAT INFLUENCE SHARES PRICE - Fanny Magdalena; Andy Andy; Vincent Winaldo; Karen Widjaja (Graduate Program of Universitas Tarumanagara, 2024)
The purpose of this study is to examine the effects of Earnings per Share (EPS) as a moderating variable on the stock price of real estate businesses listed on the Indonesia Stock Exchange (IDX) in relation to Liquidity, Profitability, and Solvency. Purposive sampling was employed in the sample selection process, and 48 data points from 16 property firm samples were used to represent the population for this study, which covered the years 2019–2021. In this study, a descriptive research design was employed. By examining relationships with other factors rather than directly comparing the variables, this descriptive study aimed to explain the presence of one or more variables. Eviews version 11 was used for data analysis in this study, whereas Microsoft Excel 2010 was employed for data processing.. This study used a random sample selection technique, namely purposive sampling. This activity was carried out from March to July 2023.